Multispectral phase shifting interferometry algorithm - Wengierow, Michal; Salbut, Leszek; Wielgus, Maciej (Photonics Letters of Poland, 2012)
Standard phase shifting interferometry (PSI) algorithms are used to obtain phase map from fringe patterns. Their spectral properties can by analyzed using frequency transform function (FTF). In this paper new multispectral phase shifting interferometry algorithm (mPSI) has been proposed. It is combination of two simpler PSI algorithms and enables filtering out unwanted high frequency fringes from the image. It can be used to increase measurement range of standard interferometry by analyzing fringe pattern created by multiplication of two other fringe patterns recorded with the use two different wavelength. Numerical simulations of mPSI algorithm and results from real setup are shown in the paper. Full Text: PDF References J. Schmit, K. Creath,"Extended averaging technique for derivation of error-compensating algorithms in phase-shifting interferometry", Appl. Opt. 34 No. 19 3610 (1995)[CrossRef] J. Schmit, K. Creath,"Window function influence on phase error in phase-shifting algorithms", Appl. Opt. 35 No. 28 5642 (1996)[CrossRef] B. S. Lee,T. C. Strand,"Profilometry with a coherence scanning microscope", Appl. Opt. 29 No. 26 3784 (1990)[CrossRef] P. Hariharan, M. Roy,"White-light Phase-stepping Interferometry for Surface Profiling", J. Mod. Opt. 41 No 11 2197 (1994)[CrossRef] H. van Brug H, R. G., "On the effective wavelength in two-wavelength interferometry", Pure Applied. Opt. 7 1465 (1998) J. C. Wyant Optical Testing: Extended Range Two-Wavelength Interferometry (Optical Sciences Center University of Arizona) J. Schmit, P. Hariharan,"Two-wavelength interferometric profilometry with a phase-step error-compensating algorithm", Opt. Eng. 45, 115602 (2006)[CrossRef] Y. Cheng, J. C. Wyant,"Two-wavelength phase shifting interferometry", Appl. Opt. 23, No 24 4539 (1984)[CrossRef] P. de Groot,"Measurement of Transparent Plates with Wavelength-Tuned Phase-Shifting Interferometry", Appl. Opt. 39, No 16 2658 (2000)[CrossRef] M. Servin, J. C. Estrada, J. A. Quiroga, "The general theory of phase shifting algorithms", Opt. Exp. 17 No 24, 21867 (2009) M. Wengierow, L. Sałbut, Z. Ramotowski,"Interferometric multiwavelength system for long gauge blocks measurements", Proc. SPIE 8082, 80822R (2011)[CrossRef]